Podcast Pedagogy: Transforming Listening Comprehension Education - Tuti Wijayanti; Nur Aeni (Balai Bahasa Sulawesi Selatan, 2024)
This study sought to determine how podcasts affected students’ listening comprehension in English-related classes. The study used a quantitative approach using a one-group pre-experimental pre-test-post-test design. Twenty seventh graders from SMPN 49 Makassar were included in the population and sample during the 2023–2024 academic year. This study tool uses questions to gauge students’ comprehension of spoken English. According to the data analysis for this study, the pre-test’s average score was 29.00, which was considered “poor,” and the post-test’s average score, which was 73.35 points, was still considered “poor.” Similarly, the significance of pvalue .000 is less than α (.05). According to the study, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected, students at SMPN 49 Makassar in seventh grade showed improved listening comprehension after receiving repeated treatments, even though it was barely significant. It comes on the surface, the mean’s classification is still “poor”, but there is still significant difference which the mean was increased from 29 to 73 with 47.35 units gain. Students show increased enthusiasm during lessons using podcasts, progressively enhancing their listening comprehension through repeated treatments. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana podcast mempengaruhi pemahaman mendengarkan siswa di kelas yang berhubungan dengan bahasa Inggris. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan desain one-group pre-experimental pre-test-post-test design. Dua puluh siswa kelas tujuh SMPN 49 Makassar dimasukkan dalam populasi dan sampel pada tahun ajaran 2023–2024. Alat belajar ini menggunakan pertanyaan untuk mengukur pemahaman siswa terhadap bahasa Inggris lisan. Berdasarkan analisis data penelitian ini, nilai rata-rata pre-test adalah 29,00 yang dianggap “buruk”, dan nilai rata-rata post-test adalah 73,35 poin, yang masih dianggap “buruk”. Demikian pula, nilai p (signifikansi) sebesar 0,000 lebih kecil dari α (0,05). Berdasarkan penelitian, hipotesis alternatif (Ha) diterima, dan hipotesis nol (H0) ditolak, siswa kelas tujuh di SMPN 49 Makassar menunjukkan peningkatan pemahaman mendengarkan setelah menerima perlakuan berulang, meskipun tidak signifikan. Terlihat bahwa klasifikasi mean masih berada pada “buruk”, namun masih terdapat perbedaan yang signifikan sehingga mean meningkat dari 29 menjadi 73 dengan perolehan 47,35 satuan. Siswa mendapatkan antusiasme di kelas saat belajar melalui podcast dan mereka mulai meningkatkan pemahaman mendengarkan mereka hari demi hari dalam perawatan.